Sickle cell disease in Madhya Pradesh, Central India: A comparison of clinical profile of sickle cell homozygote vs. sickle-beta thalassaemia individuals. Issue 9 (20th October 2016) - Yadav, Rajiv; Lazarus, Monica; Ghanghoria, Pawan; Singh, MPSS; Gupta, Rasik Behari; Kumar, Surendra; Sharma, Ravendra K.; Shanmugam, Rajasubramaniam
Abstract : Background and objectives : The clinical manifestation in sickle cell disease (SCD) patients varies from one individual to another due to factors like the presence of alpha-thalassaemia mutation, foetal haemoglobin, and β-globin gene haplotype. The present study enumerates the clinical profile of sickle cell anaemia patients from Central India. Methods : Seven hundred seventy-six SCD patients from Jabalpur and surrounding districts (Madhya Pradesh) in central India were registered with the sickle cell clinic of NIRTH, Jabalpur. The present study reveals recorded signs and symptoms of genetically confirmed sickle cell anaemia (404) and sickle beta thalassaemia (92) patients. Results : Majority of the patients were from scheduled caste communities (47.9%) and Gond tribal community (13.8%). Splenomegaly was the most common clinical manifestation observed (71.4%). Overall, 63.5% patients had a history of blood transfusion. The most frequent signs and symptoms observed were Pallor, Icterus, Joint pain, Fever, and Fatigue. Majority of the patients revealed onset of disease prior to attaining the age of 3 years (sickle cell anaemia 44.3% and sickle beta thalassaemia 35.9%). Mean haemoglobin levels among SCA individuals were marginally higher than SBT patients. On the other hand, mean foetal haemoglobin levels among SBT individuals showed the reverse trend. Notably, the present study reports the first incidence of priapism recorded in Central India. Conclusions : The study revealed a high prevalence of SCD among scheduled caste, backward caste, and tribal communities. Dissemination of study findings, screening, pre-marriage counselling, and pre-natal diagnosis are fundamental to preventing or lowering of birth of sickle cell anaemia children in the affected populations.